EFL TEACHING IN INDONESIA ELEMENTARY SCHOOL: INSIGHTS INTO GENERATION Z - Chodhori, Mutiara; Diastama, Imam Musthafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
With an emphasis on the needs of students in Generation Z, this study investigates the English instruction methods used at Elementary School in Indonesia. This study examines the materials and approaches utilized to successfully teach English, which is becoming increasingly important in today's globalized society. To further understand instructional strategies and student involvement, the study incorporates observations from classrooms as well as instructor interviews. The study, which was divided into two stages, featured observations of The teacher's class and an interview with her. The need for more participatory teaching techniques, a lack of resources, and constrained learning time are among the major issues that have been noted. The school uses the Cambridge curriculum, but it also takes Indonesia's Merdeka curriculum into account. It suggests incorporating more interactive exercises, such as games, to maintain students' interest. The results emphasize how crucial it is to modify teaching strategies to fit the demands of contemporary students and provide a welcoming environment where English can be learned successfully.